2018
DOI: 10.1002/jcp.26547
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol reverses palmitic acid (PA)‐caused TLR4‐MD2 activation‐dependent insulin resistance via disrupting MD2‐related cellular binding to PA

Abstract: Elevated plasma statured fatty acids (FFAs) cause TLR4/MD2 activation-dependent inflammation and insulin tolerance, which account for the occurrence and development of obesity. It has been confirmed that statured palmitic acid (PA) (the most abundant FFA) could bind MD2 to cause cellular inflammation. The natural compound celastrol could improve obesity, which is suggested via inhibiting inflammation, yet the detailed mechanism for celastrol is still unclear. As celastrol is reported to directly target MD2, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 42 publications
(62 reference statements)
0
16
0
Order By: Relevance
“…Studies have shown that Cel can reduce focal cerebral ischemia-reperfusion injury in rats, and the underlying mechanism may involve the inhibition of NF-κB activation, the expression of TNF-α and IL-1β, and the subsequent reduction of inflammation (Zhang et al, 2018). Yu et al (2017) (Bakar & Tan, 2017;Xiaowen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Cel can reduce focal cerebral ischemia-reperfusion injury in rats, and the underlying mechanism may involve the inhibition of NF-κB activation, the expression of TNF-α and IL-1β, and the subsequent reduction of inflammation (Zhang et al, 2018). Yu et al (2017) (Bakar & Tan, 2017;Xiaowen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…According to the recent discovery, celastrol exhibits an antitumor effect on several cancer cells through inhibiting cell survival, invasion/migration, and angiogenesis or promoting cell apoptosis in a wide variety of tumor models, including osteosarcoma, colorectal cancer, liver cancer, lung cancer, and breast cancer . Mechanically, celastrol meditates tumor‐related proinflammatory cytokines, adhesion molecules, TGF‐activated kinase 1 (TAK1), NF‐kB, CXCR4, VEGF receptor (VEGFR), proteasome, and STAT3 . Considering CCA is also an epithelial originated cancer like liver cancer or lung cancer, we hypothesized that celastrol may be an appropriate candidate for CCA treatment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in osteosarcoma, Celastrol achieves therapeutic effects by inducing the apoptosis and autophagy of cancer cells through the reactive oxygen species/c-Jun N-terminal kinase signaling pathway (Li et al, 2015 ). Additionally, Celastrol displays considerable anti-inflammatory activity (De Seabra Rodrigues Dias et al, 2017 ; Zhang et al, 2018 ) and can inhibit cellular inflammation by suppressing NLRP3 activity (Yu et al, 2017 ). Celastrol can also inhibit inflammation by inhibiting the expression of interleukin (IL)-1β (Li et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%